Effects of febuxostat on markers of endothelial dysfunction and renal progression in patients with chronic kidney disease - Naowanit Nata; Nanthawut Ninwisut; Pitchamon Inkong; Ouppatham Supasyndh; Bancha Satirapoj (Scientific Reports, 2023)
Abstract Hyperuricemia relates to chronic kidney disease (CKD) progression and impaired endothelial function. Febuxostat is potent and effective for decreasing serum uric acid levels. Information for the effect of febuxostat treatment on markers of endothelial dysfunction and renal injury among patients with CKD remains limited. A total of 84 patients with CKD stages III-IV with asymptomatic hyperuricemia were randomly assigned to either the febuxostat (40 mg/day, N = 42) or the matching control (N = 42) group for 8 weeks. Serum asymmetric dimethylarginine (ADMA), estimated glomerular filtration rate (eGFR), urine albumin, high sensitivity C-reactive protein (hs-CRP), ankle brachial index (ABI) and serum uric acid were measured at baseline and at the end of study. Febuxostat administration significantly reduced the serum uric acid concentration among patients with CKD when compared with control [− 3.40 (95% CI − 4.19 to − 2.62) vs. − 0.35 (95% CI − 0.76 to 0.06) mg/dL; P < 0.001, respectively). No significant difference in the changes in serum ADMA, hs-CRP, eGFR and albuminuria was identified between the two groups. Subgroup analysis among patients with decreased serum uric acid after febuxostat, the estimated GFR change between the febuxostat and the control group showed significant difference at 8 weeks (2.01 (95% CI 0.31 to 3.7) vs. 0.04 (95% CI − 1.52 to 1.61) mL/min/1.73 m2; P = 0.030, respectively). Adverse events specific to febuxostat were not observed. Febuxostat effectively reduced serum uric acid in the CKD population without improving endothelial dysfunction. It was able to preserve renal function in the subgroup of patients with CKD and lower serum uric acid level after treatment. Trial registration: Thai Clinical Trials, TCTR20210224005: 24/022021 http://www.thaiclinicaltrials.org/show/TCTR20210224005 .